Effects of Temperature on Male Sterility of Two Inbred Lines of Hybrid Rice - Wongpatsa, Usanee; Kaveeta, Lily; Sriwongchai, Tanee; Khamsuk, Ornusa (Agriculture and Natural Resources, 2014)
The lower critical temperature of temperature-sensitive genic male sterility (TGMS) rice is an environmental factor which has been reported to loosen the sterile pollen of the TGMS line (the A line of the 2 line hybrid system). This study investigated the effect of various temperature conditions on pollen fertility of two TGMS lines (KU-TGMS1 andKU-TGMS3) which were re-grown and transferred to a growth chamber and natural conditions (summer: April to May and winter: December to January at Kasetsart University, Bangkhen campus). Day/night temperature regimes of 26/22 °C, 26/20 °C, 24/18 °C and 22/20 °C were employed under growth chamber conditions of 11.5 hr light/12.5 hr dark and 75% relative humidity. The pollen viability and seed setting were used for male sterility identiﬁ cation. For the pollen viability test, spikelets in each line were collected from the panicle at the R3 to R4 stage. Pollen viability was examined using the I2-KI staining technique, the ﬂ uorescein diacetate staining technique, the 4’, 6-diamidino-2-phenylindole (DAPI) staining technique and the germination rate of pollen tubes. The results showed that the maximum percentage of pollen viability and seed set were found at night temperatures of 18–22 °C and 18–20 °C, respectively. For seed setting, 7.67 % was found for KU-TGMS1 at 26/20 °C and the highest seed set rate was 33.63 % for KU-TGMS3 under 24/18 °C. Testing the pollen viability with the DAPI nucleic acid staining technique and the germination rate of pollen tubes in the pistil (in vivo) was related with the seed set percentage on each line. These results indicated that the DAPI nucleic acid staining technique and the germination rate of pollen tubes in the pistil (in vivo) were suitable for viability testing of pollen in the TGMS lines and these two lines differed in critical temperature.